Evaluation of smoking cessation counseling practices of physicians working in primary health care institutions - Karacorlu, Fatma Nur; Pirincci, Edibe (Tubitak Scientific & Technological Research Council Turkey, 2024)
Background/aim: In this study, we aimed to evaluate the self -reported practice of physicians working in primary health care institutions in Elazig Province about smoking cessation counseling. Materials and methods: The population of this cross-sectional study consisted of 262 physicians working in primary health care institutions in Elazig. We aimed to reach the entire population without using the sample selection method and we successfully reached 95.42% (250 people) of the population. A questionnaire form was used for data collection. The data obtained were evaluated by frequency, percentage, mean +/- standard deviation, median and minimum-maximum, and binary logistic regression analysis. Results: The mean age of the physicians was 40.86 +/- 10.58 years and 68.0% of them were male. Among them, 30.4% (n = 76) were current smokers, 17.6% (n = 44) were former smokers and 52.0% (n = 130) were never smokers. The physicians' frequency of applying the steps of smoking cessation counseling was as follows: 38.8% Ask, 81.6% Advice, 68.4% Assess, 66.8% Assist, 31.2% Arrange. Additionally, 16.0% of the physicians received smoking cessation counseling training. Those who had not smoked at least 100 cigarettes in their life applied the Advice (p = 0.026) step more frequently. Those who received smoking cessation counseling training applied the following steps more frequently: Ask (p = 0.024), Assist (p = 0.025), and Arrange (p = 0.001). Conclusion: It is seen that the smoking frequency of primary care physicians in Elazig Province is the same as that of the general population, and the frequency of smoking cessation counseling is far behind the target. Physician population is an important target group that should not be ignored in the fight against smoking. In order to increase the frequency of physicians' smoking cessation counseling practice, there is a need to increase the number of physicians who receive smoking cessation counseling training.
Keywords: Smoking cessation; primary health care; physician; preventive health care